Environmental Challenges Faced by a Kindergarten and a School in the Katima Mulilo Education Circuit - Давид Нкенгбеза; Мундія Кілібоні Еустінах; Євген Літаба Маемеко; Муквамбо Музва (Preschool Education: Global Trends)
Introduction. A favorable educational environment – social, cultural, biological, and physical – plays a crucial role in achieving children’s academic goals. The educational environment increases children’s interest in learning. It fosters a positive attitude among children and contributes to enhancing their sense of security. However, the reality is that preschools and secondary education institutions face challenges related to administration, academic performance, attendance, and health. All these issues belong to environmental challenges.